PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII B SMP NEGERI 3 TAMBUSAI - Khairani, Khairani; Hutapea, Nahor Murani; Kartini, Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was using class action research. This research aims to fixed the process of learning and improve learning result in mathematics in grade 8B of Junior High School 3 Tambusai by applying the discovery learning model. The subject of this research were the students in the class 8B Junior High School 3 Tambusai that consist of 16 boys and 9 girls at the odd semester of academic year 2017/2018. During the learning process, there is a problem of learning that is still focused on the teacher so that students can not find the concept of learning. To solve this problem requires a learning model where students can actively discover their own learning concepts. The instruments of data collection in this research were observation sheets and a set of question description and scoring guidelines. The observation sheets were analyzed in desciptive narative, meanwhile the set of question description were analyzed in statistic desciptive. Based on the result of research, the implementation of discovery learning methods can fix the learning process and improving student’s achievement of learning mathematisc in grade 8B of Junior High School 3 Tambusai odd semester of academic year 2017/2018 on the subject matter of the function.Keywords : Students’ Math Achievement, Discovery Learning Model, Clasroom Action Research.